734 0

Q: If y/(x - z) = (y + x)/z = x/y then find z : y : x ?

  • 1
    1:2:3
  • 2
    3:2:4
  • 3
    4:3:2
  • 4
    2:3:4
  • Show AnswerHide Answer
  • Workspace

Answer : 2. "3:2:4"
Explanation :

Answer: B) 3:2:4 Explanation: Given, y/(x - z) = (y + x)/z = x/yyz = xy + x2 - yz - xz ....(1)Also xy = yx-z ⇒x2 -xz = y2 ....(2)Using (1) and (2), we get yz = xy - yz + y22yz = xy + y22z = x + y Only option (B) satisfies the equation.

Are you sure

  Report Error

Please Enter Message
Error Reported Successfully
google play

The Most Comprehensive Exam Preparation Platform

Get the Examsbook Prep App Today